2016
DOI: 10.1111/nph.13956
|View full text |Cite
|
Sign up to set email alerts
|

The evolutionary dynamics of ancient and recent polyploidy in the African semiaquatic species of the legume genus Aeschynomene

Abstract: SummaryThe legume genus Aeschynomene is notable in the ability of certain semiaquatic species to develop nitrogen-fixing stem nodules. These species are distributed in two clades. In the first clade, all the species are characterized by the use of a unique Nod-independent symbiotic process. In the second clade, the species use a Nod-dependent symbiotic process and some of them display a profuse stem nodulation as exemplified in the African Aeschynomene afraspera.To facilitate the molecular analysis of the symb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(25 citation statements)
references
References 50 publications
1
24
0
Order By: Relevance
“…By PCR, cloning, sequencing and transriptomic data analysis (see material and method section SI) using this A. evenia (CIAT22838) FEN1 sequence as basis, we obtained four different sequences of putative FEN1 genes for A. afraspera and one sequence for another A. evenia line, PI 225551. This difference in the number of FEN1 homologs between these two species is not surprising considering that A. evenia is diploid whereas A. afraspera is octoploid 16 . Phylogenetic analysis showed that all the gene products clustered in a clade containing L. japonicus FEN1 (Fig.…”
Section: Resultsmentioning
confidence: 83%
See 1 more Smart Citation
“…By PCR, cloning, sequencing and transriptomic data analysis (see material and method section SI) using this A. evenia (CIAT22838) FEN1 sequence as basis, we obtained four different sequences of putative FEN1 genes for A. afraspera and one sequence for another A. evenia line, PI 225551. This difference in the number of FEN1 homologs between these two species is not surprising considering that A. evenia is diploid whereas A. afraspera is octoploid 16 . Phylogenetic analysis showed that all the gene products clustered in a clade containing L. japonicus FEN1 (Fig.…”
Section: Resultsmentioning
confidence: 83%
“…Using the obtained sequences a phylogenetic analysis was performed as described in 16 and data are presented as rooted trees using the Cucumis IPMS as outgroup. GenBank/EMBL and Gene_ID numbers for sequences obtained and used for phylogenetic analysis can be found in Table S4 of the Supplementary information section.…”
Section: Methodsmentioning
confidence: 99%
“…For instance, some legumes have evolved the capacity to form nodules on stem tissues, in some cases with rhizobia that do not even secrete the canonical NFs (e.g. Aeschynomene; Chaintreuil et al, 2016). Variation in the legume-rhizobia interaction reflects divergent biogeographic histories (Sprent et al, 2017), independent origins of nodulation within legumes (Werner et al, 2014), and the evolution of novel plant mechanisms to better control symbionts .…”
Section: Selecting Beneficial Symbionts: One Problem Many Solutionsmentioning
confidence: 99%
“…Autopolyploidy has also been inferred through coalescent modeling in Capsella bursa‐pastoris (St. Onge et al, ) and through phylogenetic analysis of orthologous transcripts in the conifer Sequoia sempervirens (Scott et al, ). Unfortunately, extensive genomic rearrangements after WGD, as well as more recent WGDs, can obscure the nature of an ancient WGD to a point where multiple lines of evidence either cannot resolve an auto‐ or allopolyploid origin or produce conflicting results (e.g., Chaintreuil et al, ).…”
Section: Ancient Autopolyploidymentioning
confidence: 99%